1991
DOI: 10.1103/physrevlett.67.26
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of laser-stimulated radiative recombination

Abstract: Spontaneous radiative recombination between protons and electrons to form hydrogen atoms with 8<«< 19 has been measured. CO2 laser light has been shown to induce stimulated radiative recombination to the /i = 11 and 12 levels with an inferred gain in the cross section of 1720 ±860 and 4790 ±2830 for a laser power of 12.6 and 15.3 W, respectively. This is in line with that predicted theoretically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 7 publications
0
42
0
Order By: Relevance
“…The coefficients A a are tabulated for many negative ions [26]. The Fourier transform ϕ a (q) (2.13) is singular at q 2 = κ 2 with the asymptotic behavior for q → ±iκ defined by the long-range asymptote (2.14) in the coordinate spacẽ 15) where (±1) l corresponds to q → ±iκ. In particular, for a negative ion (ν = 0) with the active electron in an s state (l = 0) we have from (2.15)…”
Section: Keldysh-type Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficients A a are tabulated for many negative ions [26]. The Fourier transform ϕ a (q) (2.13) is singular at q 2 = κ 2 with the asymptotic behavior for q → ±iκ defined by the long-range asymptote (2.14) in the coordinate spacẽ 15) where (±1) l corresponds to q → ±iκ. In particular, for a negative ion (ν = 0) with the active electron in an s state (l = 0) we have from (2.15)…”
Section: Keldysh-type Approximationmentioning
confidence: 99%
“…The recent review by Hahn [8] on the electron recombination mentions only one, very special version of LAR process, namely one-photon LAR when the laser is tuned in resonance with the energy of free-bound electron transition, and only emission of photons with this particular energy is considered. The study of this special case was initiated quite long ago [9][10][11][12][13] and remains active in connection with the processes in the storage rings [14][15][16][17][18][19][20], formation of positronium [9] and antihydrogen [21][22][23] and even with possible cosmological manifestations [24]. In all these theoretical studies the laser field was presumed to be weak and its influence on an initial and/or final electron states was neglected, except Refs.…”
Section: Introductionmentioning
confidence: 99%
“…After the first successful demonstration of single-step, laser-induced recombination at the TSR storage ring at Heidelberg for protons and C 6 + [15] and for protons also in a single-path experiment [16], Borneis et al observed for the first time the real HIS analogue, the laser-stimulated twostep recombination at the ESR [17]. Figure 10 shows the arrangement.…”
Section: Laser-induced Recombinationmentioning
confidence: 99%
“…These can localize charged particles more precisely and permit optical access without restrictions enforced by large magnets. Increased overlap and localization would facilitate studies of other recombination mechanisms, such as resonantly enhanced photoinduced recombination [36][37][38]. Recombination in a smaller volume may also simplify direct laser cooling of ground-state antihydrogen that may be produced [39,40].…”
Section: Charge Densitymentioning
confidence: 99%